Study of the relationship between changes in the structural, optical, and strength properties of AlN ceramics subjected to irradiation with heavy Xe23+ ions - Bikhert, Y.V.; Kozlovskiy, A.L.; Popov, Anatoli I.; Zdorovets, M.V. (MDPI, 2023)
The purpose of this study is to comprehensively analyze the influence of different fluences of irradiation with Xe23+ heavy ions on alterations in the structural, optical, and strength properties of AlN ceramics and to establish a connection between structural distortions and alterations in the optical and mechanical properties of the ceramics. X-ray diffraction, UV-Vis and Raman spectroscopy, and indentation and single-compression methods were used as research methods. During the study, it was demonstrated that at low irradiation fluences, the main role in the changes in the properties of the AlN ceramics is played by effects related to changes in their optical properties and a fundamental absorption edge shift, which characterizes changes in the electronic properties of the ceramics (changes in the distribution of electron density). A study of the variations in the optical properties of the examined samples in relation to the irradiation fluence showed that when the fluence surpasses 5 × 1011 ion/cm2, an extra-spectral absorption band emerges within the range of 3.38–3.40 eV. This band is distinctive for the creation of vacancy ON–VAl complexes within the damaged layer’s structure. The presence of these complexes signifies structural deformations and the accumulation of defective inclusions within the damaged layer. An analysis of changes in the parameters of the crystal lattice showed that structural distortions in the damaged layer are due to the accumulation of tensile residual mechanical stresses, an increase in the concentration of which leads to the swelling and destruction of the damaged layer. Some correlations between the mechanical properties of ceramics and the irradiation fluence indicate the ceramics’ remarkable resistance to radiation-induced brittleness and weakening. These effects become apparent only when structural damage accumulates, resulting in the swelling of the crystal lattice exceeding 2.5–3%. --//-- This is an open access article: Bikhert, Y.V.; Kozlovskiy, A.L.; Popov, A.I.; Zdorovets, M.V. Study of the Relationship between Changes in the Structural, Optical, and Strength Properties of AlN Ceramics Subjected to Irradiation with Heavy Xe23+ Ions. Materials 2023, 16, 6362. https://doi.org/10.3390/ma16196362 published under the CC BY 4.0 licence.
This research was funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (No. AP14972854). In addition, A.I.P. thanks the Institute of Solid State Physics, University of Latvia, ISSP UL, as the Center of Excellence is supported through the Framework Program for European Universities, Union Horizon 2020, H2020-WIDESPREAD-01–2016–2017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project. This research was funded by Grant No. BR09158499 of the Ministry of Energy of the Republic of Kazakhstan.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; radiation damage; structural changes; deformations; heavy ions; nitride ceramics; construction materials